Localized Disseminated Tuberculosis in A 3 Year’s Old Bangladeshi Boy: A Case Study - Islam, Md. Jahedul; Farook, Saika; Karim, Md. Enamul; Yeasmin, Dilruba; Islam, Mohammad Monirul; Sarkar, Prodip Kumar (Archives of Clinical and Medical Case Reports, 2024)
Introduction and importance: An uncommon clinical variant of TB infection known as localized disseminated tuberculosis exclusively manifests as hepatic injury-related signs and symptoms with little to no extrahepatic involvement. It typically manifests as a generalized syndrome with systemic symptoms, which can occasionally create a diagnostic conundrum. It can be exceedingly challenging to make a conclusive diagnosis and calls for a high index of suspicion. Case presentation: Male Three-year-old patient was taken to the medical department because of a weeping visible lump in the disseminated TB area. Physical examination revealed nothing unusual, save for a bad overall state and hepatosplenomegaly-related discomfort. Parents say that nothing has changed over time. Yet after two weeks, the situation started to shift. Clinical Discussion: The specimen that was received in formalin with the correct lab number and the patient's identification is made up of an atypical fibrofatty piece of tissue. It is 2.5*1.5*1.0 cm in size. the gray-white sliced surface was discovered. incorporated two blocks. An inspection under a microscope revealed fibrofatty tissue that included granulation tissue. They have a significant infiltration of Lamghan's giant cells, epithelioid lesions, histiocysts, and degenerative polymorphs in certain regions. Conclusion: Atypical clinical symptoms are typically linked to tuberculosis. To confirm a diagnosis, particularly in cases of extrapulmonary TB, imaging evaluation along with histological characteristics, a high index of clinical suspicion, and improvement with antibacilar therapy are required.